THE SYSTEM OF ROLLING-STOCK’s PARAMETERS OF INTERMODAL PIGGYBACK TRANSPORTATION - A. V. Tsyganov; N. A. Osintsev (Вестник СибАДИ)
Introduction. The priority area of transport systems development is the formation of transport corridors with multimodal systems and intermodal cargo delivery technologies, ensuring the achievement of economic, social and environmental goals facing the countries. For the transport system of Russia, which claims to advance transit cargo flows through its territory, the solution to the above problems can be achieved by organization of the piggyback transportation. A necessary condition for the organization of effective piggyback transportation in domestic and international traffics is the systematization of parameters and the assessment of technical compatibility of the involved rolling-stock.Methods and models. A systems approach is used to represent piggyback transportation as a complex technical system consisting of road vehicles, domestic and foreign railway rolling-stock interacting in intermodal terminals. The ER-model is used to describe the conceptual scheme of the piggyback system.Results. The parameters of the road and railway rolling-stock are justified and systematized, their mutual influence is determined at the level of compatibility of their technical and operational parameters in the organization of domestic and international piggyback transportation. Systematization, structuring, storing and updating of rollingstock parameters are carried out using the database «Determining the rolling-stock basic parameters of piggyback delivery systems» developed in Microsoft Access.Conclusion. The developed system of parameters allows to assess technical compatibility of road and railway rolling-stock of the countries participating in piggyback transportation, and can also be used for unification of intermodal transport units and harmonization of the overall weight restrictions on the road and railway networks.Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.